Gender differences in nutritional status and determinants among infants (6–11 m): a cross-sectional study in two regions in Ethiopia - Samuel, Aregash; Osendarp, Saskia J. M.; Feskens, Edith J. M.; Lelisa, Azeb; Adish, Abdulaziz; Kebede, Amha; Brouwer, Inge D. (BMC public health, 2022)
Background A limited number of studies suggest that boys may have a higher risk of stunting than girls in low-income countries. Little is known about the causes of these gender differences. The objective of the study was to assess gender differences in nutritional status and its determinants among infants in Ethiopia. Methods We analyzed data for 2036 children (6–11 months old) collected as the baseline for a multiple micronutrient powders effectiveness study in two regions of Ethiopia in March–April 2015. Child, mother, and household characteristics were investigated as determinants of stunting and wasting. Multiple logistic regression models were used separately for boys and girls to check for gender differences while adjusting for confounders. The study is registered at http://www.clinicaltrials.gov/ with the clinical trials identifier of NCT02479815. Results Stunting and wasting prevalence is significantly higher among boys compared to girls, 18.7 vs 10.7% and 7.9 vs 5.4%, respectively. Untimely initiation of breastfeeding, not-exclusive breastfeeding at the age of 6 months, region of residence, and low maternal education are significant predictors of stunting in boys. Untimely introduction to complementary food and low consumption of legumes/nuts are significant predictors of stunting in both boys and girls, and low egg consumption only in girls. Region of residence and age of the mother are significant determinants of wasting in both sexes. Analysis of interaction terms for stunting, however, shows no differences in predictors between boys and girls; only for untimely initiation of breastfeeding do the results for boys (OR 1.46; 95%CI 1.02,2.08) and girls (OR 0.88; 95%CI 0.55,1.41) tend to be different ( p = 0.12). Conclusion In Ethiopia, boys are more malnourished than girls. Exclusive breastfeeding and adequate dietary diversity of complementary feeding are important determinants of stunting in boys and girls. There are no clear gender interactions for the main determinants of stunting and wasting. These findings suggest that appropriate gender-sensitive guidance on optimum infant and young child feeding practices is needed.